MOTS-c: A Mitochondrial-Encoded Regulator of the Nucleus - Benayoun, Bérénice A.; Lee, Changhan (BioEssays, 2019)
Mitochondria are increasingly being recognized as information hubs that sense cellular changes and transmit messages to other cellular components, such as the nucleus, the endoplasmic reticulum (ER), the Golgi apparatus, and lysosomes. Nonetheless, the interaction between mitochondria and the nucleus is of special interest because they both host part of the cellular genome. Thus, the communication between genome-bearing organelles would likely include gene expression regulation. Multiple nuclear-encoded proteins have been known to regulate mitochondrial gene expression. On the contrary, no mitochondrial-encoded factors are known to actively regulate nuclear gene expression. MOTS-c (mitochondrial open reading frame of the 12S ribosomal RNA type-c) is a recently identified peptide encoded within the mitochondrial 12S ribosomal RNA gene that has metabolic functions. Notably, MOTS-c can translocate to the nucleus upon metabolic stress (e.g., glucose restriction and oxidative stress) and directly regulate adaptive nuclear gene expression to promote cellular homeostasis. It is hypothesized that cellular fitness requires the coevolved mitonuclear genomes to coordinate adaptive responses using gene-encoded factors that cross-regulate the opposite genome. This suggests that cellular gene expression requires the bipartite split genomes to operate as a unified system, rather than the nucleus being the sole master regulator.
Keywords: Animals; Cell Nucleus; Epistasis, Genetic; Eukaryotic Cells; Gene Expression Regulation; Genome; Humans; Intracellular Signaling Peptides and Proteins; Mitochondria; Mitochondrial Proteins; RNA, Ribosomal; gene regulation; metabolism; mitochondria; mitochondrial open reading frame of the 12S ribosomal RNA type-c (MOTS-c); mitochondrial-derived peptides; mitonuclear communication; stress responses